2007
DOI: 10.1074/jbc.m703209200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Bacteriophage T4 5′ Nuclease in Complex with a Branched DNA Reveals How Flap Endonuclease-1 Family Nucleases Bind Their Substrates

Abstract: Bacteriophage T4 RNase H, a flap endonuclease-1 family nuclease, removes RNA primers from lagging strand fragments. It has both 5 nuclease and flap endonuclease activities. Our previous structure of native T4 RNase H (PDB code 1TFR) revealed an active site composed of highly conserved Asp residues and two bound hydrated magnesium ions. Here, we report the crystal structure of T4 RNase H in complex with a fork DNA substrate bound in its active site. This is the first structure of a flap endonuclease-1 family pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
80
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 55 publications
3
80
0
Order By: Relevance
“…In light of the GEN activity, Chapados et al proposed that instead of threading through the helical arch, the helical arch clamps the flap structure (35). However, a recent structure of bacteriophage T4FEN1 bound to a pseudo-Y DNA shows that the 5Ј-flap appears to pass through the arch (22). Furthermore, although a portion of the T4FEN1 arch is disordered, the 5Ј-flap makes extensive contacts with arch residues.…”
Section: The Addition Of Monovalent Salt Does Not Inhibit Hfen1-catalmentioning
confidence: 99%
See 3 more Smart Citations
“…In light of the GEN activity, Chapados et al proposed that instead of threading through the helical arch, the helical arch clamps the flap structure (35). However, a recent structure of bacteriophage T4FEN1 bound to a pseudo-Y DNA shows that the 5Ј-flap appears to pass through the arch (22). Furthermore, although a portion of the T4FEN1 arch is disordered, the 5Ј-flap makes extensive contacts with arch residues.…”
Section: The Addition Of Monovalent Salt Does Not Inhibit Hfen1-catalmentioning
confidence: 99%
“…Biochemical characterizations of FEN1 proteins from various organisms have shown that this family of nucleases can perform phosphodiesterase activity on a wide variety of substrates; however, the efficiency of catalysis on various substrates differs among the species. For instance, phage FEN1s prefer pseudo-Y substrates (22,23), whereas the archaeal and eukaryotic FEN1s prefer 5Ј-flap substrates (21,24,25), which have two dsDNA domains, one upstream and downstream of the site of cleavage, and a 5Ј-ssDNA protrusion (Fig. 1A).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Debate about the validity or otherwise of two-metal ion catalysis has focused on several enzymes including flap endonucleases (11)(12)(13)(14)(15)(16). Crystallographic studies of substrate-free FENs have demonstrated two active site-bound metal ions (14,(17)(18)(19).…”
mentioning
confidence: 99%